2008
DOI: 10.1007/s10551-008-9767-3
|View full text |Cite
|
Sign up to set email alerts
|

Faith at Work Scale (FWS): Justification, Development, and Validation of a Measure of Judaeo-Christian Religion in the Workplace

Abstract: Christianity, Faith at Work Scale, Judaism, psychometric, scale, vocation, workplace spirituality, workplace religion,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 49 publications
3
62
1
2
Order By: Relevance
“…Lin et al showed that the scale had an acceptable internal consistency and reported that its Cronbach's alpha coefficient was 0.77. It also had convergent validity with the Faith Maturity Scale [17]. In the present investigation, Cronbach's alpha of for FWS Scale was 0.86.…”
Section: Faith At Work Scale (Fws)supporting
confidence: 57%
“…Lin et al showed that the scale had an acceptable internal consistency and reported that its Cronbach's alpha coefficient was 0.77. It also had convergent validity with the Faith Maturity Scale [17]. In the present investigation, Cronbach's alpha of for FWS Scale was 0.86.…”
Section: Faith At Work Scale (Fws)supporting
confidence: 57%
“…It might be tempting to suggest that as long as you ''believe'' it does not matter if you practice. Much has been written about the boundaries among faith, religion, and spirituality (for a review of spirituality versus religion in the research of faith in the workplace, see Lynn et al, 2009). The current research used multiple methods to measure faith-related variables and found similar results among these constructs; nevertheless, researchers should continue to discover similarities and differences among these concepts.…”
Section: Research Implicationsmentioning
confidence: 80%
“…These approaches have included the definition and measurement of spirituality (Ashar and Lane-Maher 2004;Ashmos and Duchon 2000;Lynn et al 2008;Reave 2005;Seidlitz et al 2002), spirituality and organizational change (Dehler and Welsh 1994;Milliman et al 1999;Mitroff and Denton 1999;WagnerMarsh and Conley 1999), spiritual leadership as a distinct leadership style (Fry, 2003;Fry et al 2005), the influence of spiritual belief on the leader's role (McCormick 1994;Nash and McLennan 2001;Parameshwar 2005;Worden 2005), and cautions against the misuse of spirituality (Elmes and Smith 2001;Goodier and Eisenberg 2006;Nadesan 1999;Tourish and Pennington 2002).…”
Section: Spirituality and Leadershipmentioning
confidence: 99%